The «purity» of the printed page. Leopardi's annotations at a distance (Prassi Ecdotiche della Modernità Letteraria, 2018)
The essay tries to understand the reasons why Leopardi did not usually write on his books, which were part of the “sacred” body of the Family Library gathered by his father Monaldo. We can explain a few exceptions with the necessity to correct mistakes. Leopardi dialogues with his authors by incorporating some passages into his manuscript, where he feels free to comment on them.
Keywords: Leopardi; notes; annotations; comments; library